2008
DOI: 10.1063/1.2963976
|View full text |Cite
|
Sign up to set email alerts
|

High-capacity hydrogen storage by metallized graphene

Abstract: First-principles plane wave calculations predict that Li can be adsorbed on graphene forming a uniform and stable coverage on both sides. A significant part of the electronic charge of the Li2s orbital is donated to graphene and is accommodated by its distorted π * -bands. As a result, semimetallic graphene and semiconducting graphene ribbons change into good metals. It is even more remarkable that Li covered graphene can serve as a high-capacity hydrogen storage medium with each adsorbed Li absorbing up to fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
233
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 423 publications
(250 citation statements)
references
References 20 publications
16
233
0
1
Order By: Relevance
“…This optimal structure is found in the ( ) 2 3 2 3 30 R ×° supercell (Table 1), which contains 24 C and 4 Li atoms. All the Li atoms prefer to reside over hollow sites of the graphene sheet, consistent with previous results [20][21][22][23][24][25]. However, unlike uniform distribution pattern (which has symmetry group of P6mm); the four Li atoms form a rhombus structure.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…This optimal structure is found in the ( ) 2 3 2 3 30 R ×° supercell (Table 1), which contains 24 C and 4 Li atoms. All the Li atoms prefer to reside over hollow sites of the graphene sheet, consistent with previous results [20][21][22][23][24][25]. However, unlike uniform distribution pattern (which has symmetry group of P6mm); the four Li atoms form a rhombus structure.…”
Section: Resultssupporting
confidence: 80%
“…To the best of our knowledge, most of the theoretical works thus far assumed, in analogy with multilayer graphite intercalated compounds (GIC), that the Li atoms are uniformly distributed on the graphene surface [24,[27][28][29][30]. However, due to the inactive delocalized π orbitals of graphene, the diffusion barrier of Li atoms on its surface is small.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Singlelayer graphene behaved radically different instead and the intercalation stage "1", corresponding to the LiC 6 stoichio metry for the fully lithiated graphite, could not be reached. Based also on previous models developed few years before, [ 54,55 ] the authors proposed that the strong Coulombic repulsion of Li atoms facing opposite sides of the same graphene sheet results on lower binding energies, likely leading to a very low surface coverage equivalent only to a graphitic intercalation "stage 20" (i.e., stoichiometry of LiC 120 ). These fi ndings were further supported, few years later (i.e., in 2013), by a DFT study from B. I. Yakobson et al [ 56 ] showing that, in single-layer graphene, the formation of Li clusters is energetically favored with respect to any stable Li-graphene phase.…”
Section: Continuedmentioning
confidence: 99%
“…165 Theoretical predictions have shown that in Li-decorated graphene, hydrogen uptake can be increased to 12 wt% due to the induced electric eld created by Li covered graphene. 166 In addition, a model calculation on welldesigned porous graphene decorated with Li is shown to be potentially capable of adsorbing hydrogen up to 12 wt%. 167 Besides the physisorption of hydrogen on carbon surfaces, the incorporation of hydrogen into framework structures is another promising method to store hydrogen gas.…”
Section: Gas Adsorptionmentioning
confidence: 99%